Surface functionalization allowing repetitive use of optical sensors for real-time detection of antibody-bacteria interaction. - Kutscher, Marika; Rosenberger, Manuel; Schmauß, Bernhard; Meinel, Lorenz; Lorenz, Udo; Ohlsen, Knut; Hellmann, Ralf; Germershaus, Oliver (Journal of Biophotonics, 2016)
In this study, sensor surface functionalization allowing the repetitive use of a sensing device was evaluated for antibody-based detection of living bacteria using an optical planar Bragg grating sensor. To achieve regenerable immobilization of bacteria specific antibodies, the heterobifunctional cross-linker N-succinimidyl 3-(2-pyridyldithio) propionate (SPDP) was linked to an aminosilanized sensor surface and subsequently reduced to expose sulfhydryl groups enabling the covalent conjugation of SPDP-activated antibodies via disulfide bonds. The immobilization of a capture antibody specific for Staphylococcus aureus on the sensor surface as well as specific binding of S. aureus could be monitored, highlighting the applicability of optical sensors for the specific detection of large biological structures. Reusability of bacteria saturated sensors was successfully demonstrated by cleaving the antibody along with bound bacteria through reduction of disulfide bonds and subsequent re-functionalization with activated antibody, resulting in comparable sensitivity towards S. aureus.